EVALUATION OF BANANA PEEL EXTRACT AND HYDROLYSATE AS ALTERNATIVE MEDIA FOR Daphnia magna CULTURE - Musrat Jebin; Tanzila Gias; Md. Rabiul Islam; Umme Kaniz Fatema; Dinesh Chandra Shaha; Md. Amzad Hossain (Agency for Marine and Fisheries Extension and Human Resources, 2026)
The high cost and technical requirements of live-food production limit its large-scale use. Although daphnia (Daphnia magna) is a promising live feed for fish larvae, microalgal feeds commonly used for its cultivation are costly. This study aimed to assess the performance of banana peel extract (BPE) and banana peel hydrolysate (BPH) to be used as cheap alternative culture media for D. magna. D. magna was cultured for 18 days where six experimental treatments namely, T1 (D. magna cultured with live Chlorella sp., control), T2 (1% BPE), T3 (5% BPE), T4 (1% BPH), T5 (5% BPH) and T6 (1% BPE + 1% BPH) were designed with three replications each. The results indicated that population density (510.64 ± 11.07 ind. L-1) at the peak and offspring number at the first reproduction (9.50 ± 0.26 ind. L-1) in T4 were similar to those in control T1; however, significantly higher (p<0.05) than in the other treatments. Moreover, a significantly lower (p<0.05) age at first reproduction (5.47 ± 0.25 days) was recorded in T4 compared with the other treatments. Therefore, the findings of this study revealed that a 1% banana peel hydrolysate medium may provide a low-cost substrate option for D. magna culture.